2012
DOI: 10.1097/mot.0b013e328350910c
|View full text |Cite
|
Sign up to set email alerts
|

Innate cellular immunity and xenotransplantation

Abstract: Purpose of review This review assesses the recent progress in xenograft rejection by innate immune responses, with a focus on innate cellular xenoreactivity. Recent findings Current literature was reviewed for new insights into the role of innate cellular immunity in xenograft rejection. Increasing evidence confirms that vigorous innate immune cell activation is accounted for by a combination of xenoantigen recognition by activating receptors, and incompatibility in inhibitory receptor-ligand interactions. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 52 publications
1
29
0
1
Order By: Relevance
“…In the present study, the lung grafts of both recipients surviving >7 days expressed hCD47 not only on alveolar epithelium but also on the endothelium, while all other lungs lacked hCD47 expression on the endothelium, despite the expression of hCD47 in alveoli. These results are also consistent with findings from this laboratory on the role of limited cross‐species reactivity of CD47‐SIRPα interactions and on the ability of transgenic hCD47 to prevent xenograft rejection by suppressing phagocytosis of donor cells …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, the lung grafts of both recipients surviving >7 days expressed hCD47 not only on alveolar epithelium but also on the endothelium, while all other lungs lacked hCD47 expression on the endothelium, despite the expression of hCD47 in alveoli. These results are also consistent with findings from this laboratory on the role of limited cross‐species reactivity of CD47‐SIRPα interactions and on the ability of transgenic hCD47 to prevent xenograft rejection by suppressing phagocytosis of donor cells …”
Section: Resultssupporting
confidence: 91%
“…In this study, we have attempted to prolong survival of porcine XLTx in baboons by combined strategies, consisting of (i) utilizing 4 different genetically modified porcine lungs, especially focusing on the role of hCD47 expression in donor lung grafts, and (ii) utilizing an induction immunosuppressive regimen that is similar to that of the xeno‐kidney transplant model that has achieved an average of longer than 4‐month survival of life‐supporting GalT‐KO alone kidney grafts in baboons . In designing this strategy, we reasoned (i) that hCD47 expression might overcome problems caused by the known species incompatibility of porcine CD47 and the primate homolog of its ligand, signal regulatory protein alpha (SIRPα) and (ii) that hCD55 or hCD46 would mitigate the complement‐mediated effects of natural anti‐pig antibodies. We also tested whether vascularized thymic grafts from the same donors might facilitate prolonged xenograft lung survival by minimizing primate anti‐pig T‐cell responses .…”
Section: Introductionmentioning
confidence: 99%
“…However, although the use of the CRISPR/CAS9 technology has made the development of new lines of GalT-KO swine far easier than previously thought, the genes responsible for development of proteinuria has not been address by others. Recent data have found that incompatibility of a porcine CD47-baboon signal regulatory protein α (SIRP-α), which is an interspecies ligand-receptor interaction, induces activation of macrophages and phagocytosis in xenogeneic combinations (5256). Immune activation of the porcine podocyte leads to expression of CD80 which potentially downregulates SIRP-α and SMPDL-3b.…”
Section: Persistent Proteinuria Despite T-cell Unresponsivenessmentioning
confidence: 99%
“…The porcine liver has been suggested as a source of hepatocytes for bioartificial liver devices (Nicolas et al 2016) and xenografts for transplantation (Cooper et al 2015); however, these applications are controversial (Wang & Yang, 2012). Nevertheless, there is promising research on decellularized porcine hepatic lobes used for liver bioengineering (Hussein et al 2015) in which porcine tissue scaffolds are supposed to be recellularized by human hepatocytes (Wu et al 2015).…”
Section: Introduction Porcine Liver In Experimental Surgerymentioning
confidence: 99%